2017
DOI: 10.1093/mnras/stx1976
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the cosmic web

Abstract: The cosmic web is one of the most striking features of the distribution of galaxies and dark matter on the largest scales in the Universe. It is composed of dense regions packed full of galaxies, long filamentary bridges, flattened sheets and vast low density voids. The study of the cosmic web has focused primarily on the identification of such features, and on understanding the environmental effects on galaxy formation and halo assembly. As such, a variety of different methods have been devised to classify th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
285
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(313 citation statements)
references
References 194 publications
(308 reference statements)
11
285
0
Order By: Relevance
“…The principal challenge is identifying and quantifying the large-scale structure of the Cosmic Web, particularly in regions where the most diffuse gas is purported to exist. Several groups have developed automatic methods to identify large scale structures and/or derive the underlying density fields (e.g., Aragón-Calvo et al 2007;Cautun et al 2013;Sousbie et al 2011;Tempel et al 2014;Chen et al 2016;Libeskind et al 2018). The difficulty of the problem for all of these methods is compounded by the lack of a 'ground truth' solution for large-scale structures in the observed Universe.…”
Section: Introductionmentioning
confidence: 99%
“…The principal challenge is identifying and quantifying the large-scale structure of the Cosmic Web, particularly in regions where the most diffuse gas is purported to exist. Several groups have developed automatic methods to identify large scale structures and/or derive the underlying density fields (e.g., Aragón-Calvo et al 2007;Cautun et al 2013;Sousbie et al 2011;Tempel et al 2014;Chen et al 2016;Libeskind et al 2018). The difficulty of the problem for all of these methods is compounded by the lack of a 'ground truth' solution for large-scale structures in the observed Universe.…”
Section: Introductionmentioning
confidence: 99%
“…These structures, 'tendrils', have a lower density than the SDSS filaments and appear to be morphologically distinct, they are more isolated and span shorter distances. A comprehensive review and comparative analysis of these algorithms can be found in Libeskind et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, to compare our results with other methods, we also apply T-ReX on FoF halos extracted from a 200Mpc/h box of a Gadget-2 N-body simulation with 512 3 particles (Springel et al 2005). This particular simulation 2 is the one used in Libeskind et al (2017) who proposed a unified comparison of the main existing procedures to classify elements of the cosmic web using either dark matter particles or dark matter halos as input.…”
Section: Datamentioning
confidence: 99%
“…With no Article number, page 1 of 15 arXiv:1912.00732v1 [astro-ph.CO] 2 Dec 2019 A&A proofs: manuscript no. aanda aim to be exhaustive (see Libeskind et al 2017, for a detailed review about existing methods to classify cosmic web elements):…”
Section: Introductionmentioning
confidence: 99%